Pengaruh gangguan makan terhadap citra tubuh pada remaja-dewasa : Strategi intervensi meningkatkan status gizi dan kesehatan mental - Evril Katrina Riyanto; Mia Dian Prasmita; Almira Sitasari; Agus Wijanarka; Tri Siswati (DAPU Aceh Publishing, 2025)
Eating disorder is a health problem that includes various unhealthy behaviors including food restriction, overeating, and compulsive behavior related to food. The condition is often associated with mental health problems, such as anxiety and depression, and can lead to more serious eating disorders. This research method uses a comprehensive PubMed search for journals spanning 2015- 2024 found relevant research. The results is 9 articles were found regarding eating disorders, anorexia nervosa, the relationship between body shape and eating frequency, and the prevalence of eating disorders in adolescents and adults. The conclusion of this study is body acceptance therapy has been shown to be an effective and more scalable treatment option for eating disorders, thereby potentially expanding access to those in need of treatment. Given the positive initial results, further refinement and long- term follow-up are recommended to assess the sustainability of treatment results.